ANALISIS PRODUKTIVITAS ALAT PANCANG HYDRAULIC STATIC PILE DRIVER UNTUK MENINGKATKAN KINERJA WAKTU PADA PROYEK APARTEMEN APPLE 3 CONDOVILLA - Melati Puspitasari; Afrizal Nursin (Construction and Material Journal, 2021)
The selection of work methods is very important, especially inthe deep pilling installation methode. Hydraulic Static Pile Driver (HSPD) piling equipment is selected since the method uses static pressure without negative impacts (noise and vibration) for residents around the project during piling process. However, it needs to find out effective and efficient levels, and also productivity of this method. This paper will discuss the productivity and some strategies to improve duration level of pilling equipment for Apple 3 Condovilla apartment project. From analysis, it was found that the productivity value was less than one (<1) for day 2 and 4. Several factors affect the productivity of the piling equipment, such as: late start or early quits on the schedule; equipment damage, worker skills, material production, material mobilization, location of pile material, and the final set of piling. Some strategies can be performed to improve duration, such as: workers coordination workers, periodic equipment maintenance, production, mobilization, and placement of materials. Keywords: Hydraulic Static Pile Driver, Pilling, Productivity.